Re: Diagnostic accuracy of individual antenatal tools for prediction of small‐for‐gestational age at birth. B. Poljak, U. Agarwal, R. Jackson, Z. Alfirevic and A. Sharp. Ultrasound Obstet Gynecol 2017; 49: 493–499. (April 2017) - Deter, R. L.
Abstract : Linked Comment: Ultrasound Obstet Gynecol 2017; 49: 493–499